Presença de candida e de anticorpos anti-candida na cavidade bucal de pacientes com periodontite crônica do adulto - Jorge, Antonio Olavo Cardoso [UNESP] (Universidade Estadual Paulista (Unesp), 1995)
The presence of Candida and the production of histolytic enzyms by the isolated samples were observed in the saliva and gingival fluid in adult chronic periodontitis patients and health ones. It was also verified the quantity of antibodies against Candida (IgG, IgA, IgM and IgE) in the saliva and sera of the same patients through ELISA technique. Yeasts of the genus Candida mainly C. albicans were isolated from saliva in higher number from adult chronic periodontitis patients in relation to the controle with statistically significant difference. The meon of the quantity of isolated Candida (UFC/ml) were higher for periodontítis patients, although this difference was not statistically significative. Samples of Candida isolated from both groups produced hystolytic enzymes (hyaluronidase, condroitin sulfatase, proteinase, phospholipase) that are considered patogenicity factors in periodontol diseases. Only one sample of each group (C albicans) didn't produce the four analysed enzymes. The antibodies levels against Candida (IgG, IgM and IgA in saliva, IgG and IgA in sera and IgG and IgM in gingival Fluid), were statistically higher in adult chronic periodontitis patients in relation to periodontically health individuals, suggesting humoral immune response by periodontitis patients to the yeasts of the genus Candida

A presença do gênero Candida e a produção de enzimas histolíticas pelas amostras isoladas, foram observadas na saliva e no fluido gengival de pacientes com periodontite crônica do adulto e em indivíduos com periodonto saudável. Foram também verificados as quantidades de anticorpos anti-Candida as classes IgG. IgA. IgM e IgE na saliva e soro e das classes IgG. IgA e IgM no fluido do sulco gengival dos mesmos pacientes, através da reação ELISA. As leveduras do gênero Candida, principalmente C. albicans foram isoladas da saliva em maior número de pacientes com periodontite crônica do adulto em relação aos controles, com diferença estatisticamente significativa. A média da quantidade de UFC/ml de Candida isoladas, foram maiores para os pacientes com periodontite, porém esta diferença não foi estatisticamente significativa. As amostras de Candida isoladas de ambos os grupos, produziram enzimas histolíticas (hialuronidase, condroitin-sulfatose, proteinase e fosfolipase), que são considerados fatores de patogenicidade na doença periodontol. Apenas uma amostra de cada grupo (C albicans) não produziu nehuma dos quatro enzimas pesquisadas. Os níveis de imunoglobulinos anti-Candida das classes IgG. IgM e IgA na saliva, IgG e IgA no soro e IgG e IgM no fluido do sulco gengival foram estatisticamente superiores nos pacientes com periodontite crônico do adulto em relação aos indivíduos com periodonto saudável, sugerindo resposta imune humoral do organismo dos pacientes com periodontite às leveduras do gênero Candida
Keywords: Boca; Bacteriologia; Periodontite; Candida albicans; Candida; Mouth